Analysis of fretting contact by linear complementarity problem formulation - 이성철; 곽병만; 권오관 (1993)
A numerical scheme is developed for the analysis of fretting contact which is subjected to an oscillating tangential load under a bulk tension. Assuming that the contact region and the normal pressure are not influenced by the tangential load, a linear complementarity problem (LCP) formulation in an incremental form is obtained, and an equivalent minimization problem is derived from the proposed LCP. A modified simplex method is used for solving the LCP. The scheme is illustrated by typical examples of fretting contact and the effect of constant bulk tension on the fretting contact is discussed.